Associations between NLRC4 Gene Polymorphisms and Autoimmune Thyroid Disease. (4th August 2020) - Liu, Xuerong; Bai, Xiaogang; Zhao, Jing; Gao, Chaoqun; Du, Peng; Zhang, Jin-an; Li, Sheli
Abstract : Background . Many studies have shown that NLRC4 inflammasome polymorphisms are associated with a variety of autoimmune diseases, but the associations between NLRC4 polymorphisms and autoimmune thyroid diseases (AITDs) are unclear. Our research was aimed at identifying the correlations between NLRC4 polymorphisms and AITDs. Methods . Hi-SNP high-throughput genotyping technology was used for detecting four single-nucleotide polymorphisms (SNPs) of NLRC4 in 1005 AITDs patients (including 629 Graves' disease and 376 Hashimoto's thyroiditis) and 781 healthy controls. Results . Compared with healthy controls, the allele frequencies and genotype distribution of rs385076 were statistically related to AITDs (P = 0.016 and P = 0.048, respectively) and Hashimoto's thyroiditis (P = 0.022 and P = 0.046, respectively). Before adjusting for age and gender, rs385076 and AITDs had a significant association in three models of allele model, dominant model, and homozygous model. After adjusting for age and gender, in the above three models, there is still a clear relationship between them. Before adjusting for age and gender, there were prominent discrepancy between rs385076 and Hashimoto's thyroiditis in the allele model (OR = 0.81, 95% CI 0.67-0.97; P = 0.021 ) and the dominant model (OR = 0.73, 95% CI 0.57-0.94; P = 0.014 ), after adjusting for age and gender, rs385076 and Hashimoto's thyroiditis were significantly related to allele model, dominant model, and homozygous model. However, rs455060, rs212704, and rs675712 were not related to AITDs in our study. Conclusion . NLRC4 rs385076 was found to have a significant association with Hashimoto's thyroiditis for the first time. It laid a foundation for the disclosure of the pathogenesis of AITDs, and provided a possible treatment prospect for HT.